Legalisasi RUU Anti Pornografi dan Pornoaksi Dalam Perspektif Strategi Dakwah - Sahlan, Muhammad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
RUU Anti Pornography and Pomoaksi still in course of solution in DPR. At the same time many respon from various society component, both for pros and also counter. Have to be confessed that problem of pornography and pomoaksi not solely social problem, more than that - in eye glasses missionize also represent the religious problem. As nation which its resident majority Moslem people, have become the obligation for the